Tratamiento contable y tributario de las salidas de divisas en la estructura financiera en empresas consolidadoras de cargas - Morales Martillo, Andrea Noemí (2023)
The present work called "Accounting and tax treatment of foreign exchange outflows in the financial structure in cargo consolidation companies" has the purpose of analyzing the foreign exchange outflows in a cargo consolidator, due to the constant changes that tax reforms have had. with taxes on the ISD and the tax credit that can be used in exporting and importing companies. The value paid to banking entities for this generated tax would be used by a company that is responsible for consolidating charges at the international level, recording this value as a cost of sale in the statement of comprehensive income and that this affects the financial structure of the companies cargo. The sources used for the collection of information were through analysis of financial statements, interviews with employees with positions related to the study area, audit reports, to know the reality regarding the presentation and reliability of financial information, ending with the respective conclusions and recommendations.